Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.3201/eid1003.020713
|View full text |Cite
|
Sign up to set email alerts
|

Acute Spotted Fever Rickettsiosis among Febrile Patients, Cameroon

Abstract: Although potential arthropod vectors are abundant in Cameroon, acute febrile illnesses are rarely evaluated for arboviral or rickettsial infections. Serum samples from 234 acutely febrile patients at clinics in Tiko and Buea, Cameroon, were examined for antibodies to Rickettsia africae and African alphaviruses and flaviviruses. These serum samples did not contain antibodies against typhoid, and blood malarial parasites were not detected. Serum samples of 32% contained immunoglobulin M antibodies reactive with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 25 publications
6
64
0
Order By: Relevance
“…The report based on a serologic survey that used an unreliable technique demonstrated rickettsial antibodies in cattle and humans in the northern region of Cameroon and in other animals in the south of the country ( Maurice et al, 1968;Le et al, 1977). Efforts to determine the epidemiology and ecology later re-emerged in 2004 when anti-rickettsial IgM antibodies were detected in some Cameroonian patients along the coastal region of Cameroon (Ndip et al, 2004a). These results were further confirmed by detection of R. africae DNA in about 6% of acutely ill febrile patients (Ndip et al, 2004b).…”
Section: Epidemiologysupporting
confidence: 56%
See 2 more Smart Citations
“…The report based on a serologic survey that used an unreliable technique demonstrated rickettsial antibodies in cattle and humans in the northern region of Cameroon and in other animals in the south of the country ( Maurice et al, 1968;Le et al, 1977). Efforts to determine the epidemiology and ecology later re-emerged in 2004 when anti-rickettsial IgM antibodies were detected in some Cameroonian patients along the coastal region of Cameroon (Ndip et al, 2004a). These results were further confirmed by detection of R. africae DNA in about 6% of acutely ill febrile patients (Ndip et al, 2004b).…”
Section: Epidemiologysupporting
confidence: 56%
“…The agent was later isolated in A. hebraeum ticks in Zimbabwe in 1990, and in 1992, the first isolate from a patient was obtained Kelly et al, 1994). The pathogen has been detected in many other African countries including Senegal , Ethiopia (Stephany et al, 2009) and Cameroon (Ndip et al, 2004a;Ndip et al, 2004b). In the following, we give a synopsis of our current knowledge of African tick bite fever in Cameroon.…”
Section: The Genus Rickettsiamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite high seroprevalence to R. africae among native Africans, nearly all acute cases of ATBF described in the literature have occurred in European or American travelers (145,205,273). Recently however, Ndip et al reported cases of ATBF documented by serology (26 patients) and molecular techniques (7 patients) among indigenous patients in Cameroon (212,213).…”
Section: Emerging Pathogens (1984 To 2004)mentioning
confidence: 99%
“…Unfortunately, after the last (1976) publication of these surveys, there was a 25-year gap before Fontenille and Toto reported the introduction of the Aedes albopictus, a potential new vector of DF and YF into southern Cameroon (6)(7)(8). Later, Ndip et al (9) Kuniholm et al (10) and Demanou et al (11), reported prevalence of antibodies (Abs) to some arboviruses in the serum of febrile patients in Cameroon, and Peyrefitte et al, isolated the CHIKV from a patient. In this survey, we sought to further investigate the latent circulation of arboviruses, characterise the agents and assess the risk of infection in Cameroon, with reference to the Fako Division ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%